Rapidly cleared episodes of herpes simplex virus reactivation in immunocompetent adults - Mark, Karen E; Wald, Anna; Magaret, Amalia S; Selke, Stacy; Olin, Laura; Huang, Meei-Li; Corey, Lawrence (The Journal of infectious diseases, 2008)
Herpes simplex virus (HSV) remains latent in nerve root ganglia of infected persons and is thought to reactivate several times yearly. Recent in situ data show the localization of HSV-specific CD8(+) T cells at the dermal epidermal junction next to peripheral sensory nerve endings, suggesting that viral reactivation may occur more frequently than previously appreciated. Twenty-five HSV-2-seropositive and 18 HSV-1-seropositive healthy adults collected anogenital and oral swabs, respectively, 4 times per day for 60 days. Swabs were assayed for HSV, using a quantitative polymerase chain reaction assay. Twenty-four percent of anogenital reactivations and 21% of oral reactivations lasted < or =6 h, and 49% of anogenital reactivations and 39% of oral reactivations lasted < or =12 h. Lesions were reported in only 3 (7%) of 44 anogenital reactivations and 1 (8%) of 13 oral reactivations lasting < or =12 h. The median HSV DNA levels at initial and last detection were 10(3.5) and 10(3.3) copies/mL, respectively, during anogenital reactivation and 10(3.7) and 10(3.0) copies/mL, respectively, during oral reactivation. This high frequency of short subclinical HSV reactivation in immunocompetent hosts strongly suggests that the peripheral mucosal immune system plays a critical role in clearing HSV reactivations.